Pemodelan Pengeringan Polyvynil Alcohol dalam Larutan Organik dengan Reaction Engineering Approach (REA) - Geraldy Suhendro (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Drying is water removal process involving mass and heat transfer simultaneously. The accurate drying model can be used to assist in process design and monitoring the quality of the product. The Reaction engineering approach (REA) have been proven for various drying chases involving water removal. In this study, the REA is develop to model removal of non-water solvent. The REA is implemented for convective and intermittent drying of polyvinyl alcohol from organic solvent which is a mixture of water and methanol. In order for REA modification, a minor modification of the equilibrium activation energy is introduced since there are two kinds of solvent in a mixture. Equilibrium activation energy was determined from the final product temperature and corresponding humidity of air. The results of the modeling match well with the experimental data. The REA can model the drying of the organic solvent accurately. The REA can be used for troubleshooting and optimization in organic solvent drying.